Extraction and characterization of microcrystalline cellulose from kelp (Laminaria japonica) waste - Zhenhua Liu; Wei Xie; Lan Ye; Chaojie Chen (PLoS ONE, 2026)
Kelp, an economically important brown alga widely cultivated in East Asia, produces kelp waste rich in cellulose as a byproduct of alginate extraction. In this study, kelp cellulose (KC) was first extracted from the kelp waste. Subsequently, 2 wt% hydrochloric acid was used to hydrolyze the kelp cellulose at 100 °C for 30 min to isolate kelp microcrystalline cellulose (KMCC) from the KC. Characterization by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) revealed that the chemical structures and cellulose I crystal form remained intact during hydrolysis, with the crystallinity index increasing from 76.4% to 78.1%. Thermogravimetric analysis (TGA) and derivative TGA indicated enhanced thermostability of KMCC compared to KC. Scanning electron microscopy (SEM) observations showed that acid hydrolysis transformed the irregular thin-sheet structure of KC into smaller-sized KMCC with a morphology distinct from the rod-like structure of commercial microcrystalline cellulose (CMCC). The level-off degree of polymerization (LODP) of KMCC measured around 164.3, closely resembling the value for CMCC at 166.5, with a yield of 85.5%. This study proposes a novel method to utilize kelp waste by converting it into MCC, offering a potential avenue for its valorization.